Effectiveness of Concept Attainment Model on Mental Process and Science Ability - Singh*, Pawan Kumar (Recent Research in Science and Technology, 2011)
Model of teaching is an innovative method of teaching. A variety of teaching approaches have been evolved to design instruction. But which approach/ Model of teaching is most appropriate, having better impact effective, efficient, interesting?.....! can only be answered through research keeping each Model’s instructional and nurturant effects in view. A step was needed to prove effect of Concept Attainment Model on mental processes and attitude towards science and the like. Therefore the present investigator undertook the problem of evaluating the effectiveness of Concept Attainment Model on mental process and science ability. Thus the present study can be stated as ’’Effectiveness of Concept attainment Model in mental process and science Ability’’.